What the eyes don't see : a story of crisis, resistance, and hope in an American city - Hanna-Attisha, Mona (New York : One World, 2018)
"From the heroic pediatrician who rallied a community and brought the fight for justice to national attention comes a powerful firsthand account of the Flint water crisis--a dramatic story of failed democracy and inspiring citizen advocacy and action. In the heart of the world's wealthiest nation, one hundred thousand people were poisoned by the water supply for two years--with the knowing complicity of their government. Written by the crusading pediatrician who helped turn the crisis into a transformative movement for change, What the Eyes Don't See is a devastating insider chronicle of the Flint water crisis, the signature environmental disaster of our time, and a riveting narrative of personal advocacy. Here is the dramatic story of how Dr. Mona used science to prove Flint kids were exposed to lead, and how she courageously went public with her research and faced a brutal backlash. With persistence and single-minded sense of mission, she spoke truth to power. The book explores the horrific reality of how misguided austerity policies and callous bureaucratic indifference placed an entire city at risk. A medical and scientific thriller, What the Eyes Don't See grapples with our country's history of environmental injustice while telling the inspiring personal story of Dr. Mona--an immigrant, a doctor, and a scientist--whose family roots in social justice activism buoyed her through the fight for justice in Flint. It captures a timely and essential story of how communities can come together to fight for social justice, even in opposition to their own governments"--
Includes bibliographical references (pages 335-352) and index.
Keywords: Hanna-Attisha, Mona; Lead poisoning -- Michigan -- Flint; Drinking water -- Lead content -- Michigan -- Flint; Water quality management -- Michigan -- Flint; Physicians -- Michigan -- Flint -- Biography; SCIENCE / Environmental Science; MEDICAL / Public Health; SOCIAL SCIENCE / Sociology / Urban; Flint (Mich.) -- Environmental conditions